The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1590/2318-0331.231820170109
|View full text |Cite
|
Sign up to set email alerts
|

Proposal of rainwater harvesting coefficient (RWHC) for determination of effectively usable rainfall depth, relevant to rainwater harvesting systems design

Abstract: The study measures rainfall data to determine a rainwater harvesting coefficient revelant to rainwater harvesting and catchment projects assisted by non-parametric statistics tests, based on assumption that part of the total rainfall depth is discarded. The analyses of historical rainfall series shows that the city of Belem presents large potential to promote rainwater harvesting, with a rainy season and a less rainy season during the year. The results present an average of one rainfall event per day, from Jan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…From Figure 4 it is possible to observe that for the same storage tank volume, the failures on demand-supply are greater when the first-flush diverter is considered by comparing with a non-diverter system, agreeing with results presented by Corrêa et al (2018) and Semaan et al (2020). Specifically, for the 200 m 2 rooftop area, the introduction of a first-flush diverter means to discard a volume that can reach 0.4 m 3 every 7 days.…”
Section: First-flush Divertersupporting
confidence: 82%
See 2 more Smart Citations
“…From Figure 4 it is possible to observe that for the same storage tank volume, the failures on demand-supply are greater when the first-flush diverter is considered by comparing with a non-diverter system, agreeing with results presented by Corrêa et al (2018) and Semaan et al (2020). Specifically, for the 200 m 2 rooftop area, the introduction of a first-flush diverter means to discard a volume that can reach 0.4 m 3 every 7 days.…”
Section: First-flush Divertersupporting
confidence: 82%
“…The analysis accomplished indicated that daily rainfall time series are suitable for RWH system design in the evaluated cities and were also adequate for Belém, State of Pará, Brazil (Corrêa et al, 2018). The use of daily rainfall time series is also an international recommendation, as stated by Campisano et al (2017).…”
Section: /16mentioning
confidence: 85%
See 1 more Smart Citation